2016
DOI: 10.1093/ageing/afw081
|View full text |Cite
|
Sign up to set email alerts
|

How effective is integrated care for community-dwelling frail older people? The case of the Netherlands

Abstract: Integrated care programs have been developed to enhance the quality care for older adults in primary care. These programs usually consist of a multidisciplinary approach, with personalised care based on comprehensive geriatric assessments. However, there is limited evidence for the effectiveness of these programs in frail older people. In this article, we review the results of three recent intervention studies carried out as part of the Dutch National Care for the Elderly Programme. The results illustrate how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
43
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 16 publications
4
43
0
1
Order By: Relevance
“…An earlier meta-analysis of 24 trials of geriatric assessment of people selected as frail reported a small effect on hospital admissions only 30. Three later randomised trials of CGA in the Netherland’s frailty care programme found almost no clinical benefits 31. Available evidence for cost effectiveness is inconsistent and inconclusive 173132…”
Section: Challenges To Adopting the Frailty Agenda In Primary Carementioning
confidence: 99%
See 1 more Smart Citation
“…An earlier meta-analysis of 24 trials of geriatric assessment of people selected as frail reported a small effect on hospital admissions only 30. Three later randomised trials of CGA in the Netherland’s frailty care programme found almost no clinical benefits 31. Available evidence for cost effectiveness is inconsistent and inconclusive 173132…”
Section: Challenges To Adopting the Frailty Agenda In Primary Carementioning
confidence: 99%
“…Three later randomised trials of CGA in the Netherland’s frailty care programme found almost no clinical benefits 31. Available evidence for cost effectiveness is inconsistent and inconclusive 173132…”
Section: Challenges To Adopting the Frailty Agenda In Primary Carementioning
confidence: 99%
“…Evaluations of these initiatives have established potential benefits of greater levels of service integration, but they have also highlighted limitations. For instance, evidence for the effectiveness of integrated care programmes for older people living at home remains inconsistent [1427]. Also, knowledge of how to successfully implement and improve integrated care is still limited, as is knowledge of how to transfer these experiences to other contexts [28].…”
Section: Introductionmentioning
confidence: 99%
“…Also, knowledge of how to successfully implement and improve integrated care is still limited, as is knowledge of how to transfer these experiences to other contexts [28]. Furthermore, improvements to the current way of working in existing initiatives are considered necessary, to make them more person-centred, prevention-oriented, safe and efficient [2427293031]. In addition, more insight into how to measure and evaluate (improvements in) integrated care programmes is needed to be able to capture outcomes and processes adequately and consistently across different programmes and evaluation studies.…”
Section: Introductionmentioning
confidence: 99%
“…The aim of such programs is to prevent loss of autonomy and worsening of disability by initiating the care process before older people express explicit demand (Huss, Stuck, Rubenstein, Egger, & Clough-Gorr, 2008; Liebel, Friedman, Watson, & Powers, 2009; Stuck, Egger, Hammer, Minder, & Beck, 2002). However, evaluations of the effectiveness of proactive home visit programs in systematic literature reviews and meta-analyses yield inconsistent results: Some individual studies report positive effects on patient outcomes such as functional status, mental health, and perceived social support, whereas others find no results at all (Elkan et al, 2001; Hoogendijk, 2016; Huss et al, 2008; Marek & Baker, 2006; Markle-Reid et al, 2006; Stuck et al, 2002). So far, this inconsistency remains poorly understood: Differences in study design, program characteristics, target populations, and context complicate the investigation of what program components contribute to a change in outcomes (Huss et al, 2008; Liebel et al, 2009; Markle-Reid et al, 2006).…”
Section: Introductionmentioning
confidence: 99%